El legado de Schumpeter al estudio de la administración de empresas - Berumen, Sergio A. (Universidad ESAN. ESAN Ediciones, 2007)
In this article it is stated that the most demonstrated statements of the neoschumpeterian theory might be extremely useful for the analysis of business administration. Schumpeterian theory focuses in the use of analogies or biology concepts to analyze the behavior of institutions and social systems. For this focus, the signals that companies receive from the economical system are of three types: a) the technological opportunities and the benefits expected, which are closely related to them, b) the current behavior and the expected one from the demand from its products and other products and c) the changes in costs, prices, quantities, and rentabilities in the markets in which they operate, and in some others.

En este artículo se expone cómo los planteamientos más sólidos del pensamiento neoschumpeteriano pueden ser de suma utilidad para el análisis de la administración de empresas. La teoría schumpete-riana se centra en el uso de conceptos de la Biología para analizar, por analogía, el comportamiento de las instituciones y los sistemas sociales. Según este enfoque, las señales que las empresas reciben del sistema económico son de tres tipos: a) las oportunidades tecnológicas y los benefi cios esperados asociados a ellas, b) el comportamiento actual y esperado de la demanda por sus productos y por otros productos y c) los cambios en costos, precios, cantidades y rentabilidades en los mercados donde operan y en algunos otros.
Keywords: Neoschumpeterian theory; Business administration; Pensamiento neoschumpeteriano; Administración de empresas; Organizations; Organizaciones; https://purl.org/pe-repo/ocde/ford#5.02.04